Binding to Gating Transduction in Nicotinic Receptors: Cys-Loop Energetically Couples to Pre-M1 and M2–M3 Regions - Lee, Won Yong (Society for Neuroscience, 2009)
The nicotinic acetylcholine receptor (AChR) transduces binding of nerve-released ACh into opening of an intrinsic ion channel, yet the intraprotein interactions behind transduction remain to be fully elucidated. Attention has focused on the region of the AChR in which the β1–β2 and Cys-loops from the extracellular domain project into a cavity framed by residues preceding the first transmembrane domain (pre-M1) and the linker spanning transmembrane domains M2 and M3. Previous studies identified a principal transduction pathway in which the pre-M1 domain is coupled to the M2–M3 linker through the β1–β2 loop. Here we identify a parallel pathway in which the pre-M1 domain is coupled to the M2–M3 linker through the Cys-loop. Mutagenesis, single-channel kinetic analyses and thermodynamic mutant cycle analyses reveal energetic coupling among αLeu 210 from the pre-M1 domain, αPhe 135 and αPhe 137 from the Cys-loop, and αLeu 273 from the M2–M3 linker. Residues at equivalent positions of non-α-subunits show negligible coupling, indicating these interresidue couplings are specific to residues in the α-subunit. Thus, the extracellular β1–β2 and Cys-loops bridge the pre-M1 domain and M2–M3 linker to transduce agonist binding into channel gating.